PENGARUH UKURAN PERUSAHAAN DAN REPUTASI KANTOR AKUNTAN PUBLIK (KAP) TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - FENTY ASTRINA; RESMADELY RESMADELY (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2020)
This study aims to determine the size of the company and the reputation of the firm affect the audit delay on conventional banking sector companies listed on the Indonesia Stock Exchange in 2014-2018. The population of this study is the banking sector companies listed on the Indonesia Stock Exchange and the annual reports from 2014 to 2018 with a total sample of 28 conventional banking sector companies. The data used in this study are data on annual financial statements and audited financial statements of companies obtained from 2014 - 2018 published at www.idx.co.id. Data analysis and discussion are carried out using quantitative and qualitative methods to test the truth of hypotheses. The results showed that company size and KAP's reputation affected audit delay in conventional banking sector companies on the Indonesia Stock Exchange.